PERANAN TOKOH DALAM TATA RUANG PERMUKIMAN MASA MATARAM ISLAM DARI SITUS POTORONO - Abdul Choliq Nawawi (BRIN, 1995)
Based on the large number of Hinduistic socio-cultural artifacts in the Potorono settlement group, namely at the Botokan, Potorono Kidul, Potorono Lor, and Mayungan sites as centers for the remains of monumental buildings such as Hinduistic temples, it can be concluded tentatively that the Potorono settlement belongs to the classical period. Furthermore, it is assumed as a core settlement in the Hinduistic socio-cultural layer.